2018
DOI: 10.1038/s41598-018-30547-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrative metagenomic and biochemical studies on rifamycin ADP-ribosyltransferases discovered in the sediment microbiome

Abstract: Antibiotic resistance is a serious and growing threat to human health. The environmental microbiome is a rich reservoir of resistomes, offering opportunities to discover new antibiotic resistance genes. Here we demonstrate an integrative approach of utilizing gene sequence and protein structural information to characterize unidentified genes that are responsible for the resistance to the action of rifamycin antibiotic rifampin, a first-line antimicrobial agent to treat tuberculosis. Biochemical characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Here, we observed that this H-Y-[QED] motif is highly conserved in almost all hundreds of Arr sequences analyzed, indicating its importance in Arr activity, and suggesting that these Arr sequences could be functional. Indeed, the Arr enzymes already functionally characterized (Arr-ms, Arr-2 to Arr-8, Arr-cb, Arr-sc, Arr_Mab, Arr-wd1-4) 2 , 4 , 6 8 and those of the present study were observed along the phylogenetic tree, showing that despite the sequence diversity, even in the RIF binding sites, their activities against rifamycins are maintained. These patterns were observed in sequences carried by bacteria belonging to high and low antibiotic-impacted environments.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…Here, we observed that this H-Y-[QED] motif is highly conserved in almost all hundreds of Arr sequences analyzed, indicating its importance in Arr activity, and suggesting that these Arr sequences could be functional. Indeed, the Arr enzymes already functionally characterized (Arr-ms, Arr-2 to Arr-8, Arr-cb, Arr-sc, Arr_Mab, Arr-wd1-4) 2 , 4 , 6 8 and those of the present study were observed along the phylogenetic tree, showing that despite the sequence diversity, even in the RIF binding sites, their activities against rifamycins are maintained. These patterns were observed in sequences carried by bacteria belonging to high and low antibiotic-impacted environments.…”
Section: Discussionmentioning
confidence: 49%
“…Highly conserved residues (≥ 90%), considering all Arr sequences analyzed in the phylogeny, are represented below the alignment by the fuchsia blocks. References: Arr-2, Arr-sc, and Arr-ms 1 ; Arr-4 and Arr-5 6 ; Arr-8 8 ; Arr-w1, Arr-w2, Arr-w3, and Arr-w4 4 ; ArrMab 7 ; Arr-cb 2 . …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations